Pembelajaran Berdiferensiasi Menggunakan Model Problem Based Learning Serta Pemanfaatan Platform Quizizz Sebagai Asesmen - Nasution, Lukas; Asriati, Nuraini (Universitas Tanjungpura, 2024)
The education sector in Indonesia has entered a new phase. In the wake of the COVID-19 pandemic, the educational paradigm has undergone significant changes. Many activities that were previously conventional have now shifted towards requiring digital platforms to support their processes. One notable change is the integration of digital technology into education. In response to these opportunities and challenges, the author conducts research entitled